Enhancing Critical Thinking Skills through Expository Text Media - Nuril Izzah (Program Studi Pendidikan Guru Madrasah Ibtidaiyah INSURI Ponorogo, 2024)
The low level of students' critical thinking skills negatively impacts the Literacy Development Index. Critical thinking is a solution for developing literacy skills; in other words, if students possess strong critical thinking abilities, the Literacy Index will improve. This study aims to analyze the effect of intensive reading activities using expository texts on students' critical thinking skills. This research employs a quantitative approach with a true experimental design, specifically a pretest-posttest control group design. Data collection methods include observation and tests, analyzed using SPSS version 27. The research was conducted at Madrasah Ibtidaiyah Negeri 2, Bogor Regency, with a sample size of 47 students. The analysis conducted includes: 1) descriptive analysis, which describes research variables through percentages, and 2) t-test to statistically compare the two groups. The results indicate that the experimental group achieved a higher percentage of critical thinking skills than the control group. The post-test scores of the experimental group were significantly higher, demonstrating a positive impact and significant improvement in students' critical thinking skills facilitated by intensive reading techniques using expository texts. This study concludes that learning activities utilizing intensive reading techniques effectively enhance students' critical thinking skills. Consequently, improving students' critical thinking skills will contribute to advancements in the Literacy Development Index.